Using the multiliteracies approach to promote English literacy in higher education / Sarjit Kaur and Gurnam Kaur Sidhu - Kaur, Sarjit (ACRULeT, Faculty of Education & UiTM Press, 2007)
Higher education teachers who teach English proficiency courses to undergraduates often make the assumption that if learners work hard on content taught to them, they would have acquired literacy in all aspects relating to the language. Do learners’ abilities to read well or write well in English depend on their context? To discern the appropriate path for their learners, higher education teachers must be knowledgeable about “language and literacy, be adept at seeking and critically evaluating information and be able to relate these understandings to their daily working knowledge of their learners” (Heydon, Hibbert & Iannaci, 2005: 312). Many definitions of the term ‘literacy’ seem to focus too much on skill to the exclusion of will (Padak & Bardine, 2004). The concepts of promoting ‘engaged learners’ and ‘literacy empowerment’ in higher education contexts should incorporate some of the following aspects: motivation, strategies, knowledge and social interaction. This paper discusses the design and framework of the Multiliteracies Approach advocated by The New London Group and argues that it is a viable teaching strategy that embraces literacy abilities, literacy choices and attitudes. Additionally, it recognizes that meaningful learning can take place if there is bridging between theory and practice.